ADMINISTRATION AND LOCAL ECONOMIC DEVELOPMENT CASE STUDY: VALCEA COUNTY - Aurelia-Camelia MARIN (Strategii Manageriale)
Involving local governments is one of the key issues and challenges for the development of each region, not least for the development of Romania, as an EU member country. The main purpose of this paper is to identify the main factors affecting the ability of local authorities in Romania, especially those in Valcea county to provide economic operators and citizens conducting an environment of economic activities and a high level of quality of life. For example, I follow the development of several economic indicators relevant for economic development and opportunities for involvement of local government to improve the economic situation specific to this county. As research methods in paper I plugged classification, synthesis, static and dynamic comparative analysis, methods of induction and deduction, the graphical representation of events and phenomena investigated in an attempt to provide an explanation of the problem that is, in terms theoretically convincing.